Perspectiva realista da filosofia de Karl-Otto Apel - Silva, Antonio Wardison Canabrava da (2019)
This thesis aims to demonstrate the realist perspective of Karl-Otto Apel's philosophy. In this sense, it will seek to answer the following question: Does Apel, when overcoming nominalism, as it is presumed, architect a philosophy from a realist perspective? Such questioning will enable the comprehension of how Apel, on the one hand, structures his thinking in a profound dialogue with the most distinct modern and contemporary philosophers, and, on the other hand, absorbs a realist perspective within his philosophical legacy. To accomplish this task, the first part will analyze the pre-semiotic epistemology: nominalism. The first chapter will engage in a discussion with analytical philosophy, from its main representative, Wittgenstein; the second, with hermeneutic philosophy, based on Heidegger. It is, respectively, a critical analysis about the ambiguity, unfolding and attempt to solve the analytical philosophy and the hermeneutic and critical tradition of meaning, perspectives which are considered abstract by Apel and, therefore, unable to speculate on the meaning and validity of truth. The second part will discuss the semiotic-pragmatic epistemology: realism. The third chapter will address the foundations of Apel's philosophy, which consists in the semiotic transformation of Kant's transcendental logic. Apel, with Peirce, attempts to answer the Kantian question about the conditions of possibilities and validity of knowledge. He develops, therefore, a hermeneutical perspective for the unlimited community of communication; the fourth and fifth chapters reflect on the fundamental elements of Apel's philosophy: the transcendental-hermeneutic concept of language, the theory of truth, the ultimate foundation of philosophy, and the ethics of speech. Those chapters seek to demonstrate, as can be presumed, the realist perspective of Apel's philosophy, that is to say, the phenomenological character – hence not restricted to anthropology or epistemology, not even to metaphysics – within his thinking. Apel develops a philosophy in the context of the twentieth-century linguistic turn as a transformation of the metaphysical and transcendental tradition. With and beyond Kant, Wittgenstein, Heidegger, Peirce, Gadamer, and others, he develops a postconventional philosophy characterized by transcendentally mediated language in search of consensus, as opposed to methodical solipsism and scientific neutrality. It thus constitutes a transcendental-semiotic philosophy, developed within language, intersubjective, in close connection with the real world and, therefore, a philosophy from a realist perspective